Dor e desempenho físico em idosos comunitários - resultados do International Mobility in Aging Study (IMIAS) - Silva Júnior, Edmilson Gomes da (2021)
Introduction: the population aging process has an impact on the increasing prevalence of disabling conditions for the elderly people. Chronic pain in older people is considered a public health problem, causing high demand for health services, and being associated with physical and functional disability. The prevalence of painful symptoms and mobility deficits vary in aging populations from different social contexts. However, there are gaps in knowledge about the intervening factors of the association of pain with functionality in the elderly. Objectives: To estimate the prevalence of painful symptoms in a population sample of countries with different aging profiles; and to identify the factors associated with pain in relation to physical performance considering the confounding factors. Methodology: This is a cross-sectional study nested within a cohort study, o International Mobility in Aging Study (IMIAS), carried out in the cities of Saint-Hyacinthe (Quebec, Canada), Kingston (Ontario Canada), Manizales (Colombia), Tirana (Albania) and in Natal (Brazil). Data on 1725 elderly people aged 65 to 74 years obtained in the 04 countries of the study were evaluated. Socioeconomic data, health and anthropometric measurements were collected. Physical performance was assessed using the Short Physical Performance Battery (SPPB), and painful symptoms, by self-reported presence of back and lower limb pain. Results: men had a lower prevalence of pain when compared to women, with the lower limbs region being more affected (p <0.001). In performance assessment, men obtained the best average of the total SPPB score in relation to women (p <0.001). Painful symptoms was associated with poor physical performance in the elderly in both sexes (p <0.001). Variables linked to health status, such as the presence of depressive symptoms, body mass index were associated with low physical performance in women (p <0.001), the same observed in relation to socioeconomic conditions (p <0.001). Conclusion: Pain proved to be a limiting factor for the physical performance of the population of the elderly studied, and it was associated to health and socioeconomic conditions.